2014
DOI: 10.2147/ceg.s55410
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin (5-HT3) receptor antagonists for the reduction of symptoms of low anterior resection syndrome

Abstract: PurposeSerotonin (5-hydroxytryptamine [5-HT])3 receptor antagonists are effective for the treatment of diarrhea-predominant irritable bowel syndrome (IBS-D), in which exaggerated intestinal/colonic hypermotility is often observed. Recent studies have suggested that the motility disorder, especially spastic hypermotility, seen in the neorectum following sphincter-preserving operations for rectal cancer may be the basis of the postoperative defecatory malfunction seen in these patients. We investigated the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…In minor-LARS patients, medical management is advised; however, few high-quality data are available regarding this matter. Loperamide treatment for diarrhoea, 5-HT 3 receptor antagonists for postprandial urgency and incontinence, and simethicone for gas and bloating remain the treatments of choice in this group of patients [ 18 – 21 ]. Dietary restrictions, high fibre consumption, and probiotics are advised, although no data support the benefit of those agents.…”
Section: Discussionmentioning
confidence: 99%
“…In minor-LARS patients, medical management is advised; however, few high-quality data are available regarding this matter. Loperamide treatment for diarrhoea, 5-HT 3 receptor antagonists for postprandial urgency and incontinence, and simethicone for gas and bloating remain the treatments of choice in this group of patients [ 18 – 21 ]. Dietary restrictions, high fibre consumption, and probiotics are advised, although no data support the benefit of those agents.…”
Section: Discussionmentioning
confidence: 99%
“…Itagaki et al [25] investigated whether serotonin (5-HT3) receptor antagonists, which are known to be effective in treating patients with irritable bowel syndrome, might be effective in treating patients with LARS. Based on all parameters, including incontinence score, urgency grade, and the number of toilet visits per day, they demonstrated that 5-HT3 antagonists were effective in treating patients with LARS.…”
Section: Treatment Of Larsmentioning
confidence: 99%
“…Research has proposed that the expression of 5-HT is significantly reduced in patients with anterior rectal resection, which may be related to the pathogenesis of ARS [ 20 ]. Serotonin, a 5-HT3 receptor antagonist, has been proved to relieve the symptoms of low anterior resection syndrome [ 21 ]. The role of 5-HT in the intestinal tract is generally considered as a neurotransmitter that promotes intestine to function normally, and it is also one of the signal sources of TRPV function (a proton and heat-gated channel) mediated in the intestinal lumen [ 22 ].…”
Section: Discussionmentioning
confidence: 99%